Looking for the optimum security architecture in Europe: EU and NATO – together or apart? - J. Yu. Melnikova (Международная аналитика, 2021)
The recent years saw the most turbulent period of transformation of the liberal world order since the end of the Cold War. This directly aff ects transatlantic relations, historically serving as a beacon of the Washington’s foreign policy. This notwithstanding, while the U.S. foreign policy priorities have been changing, the members of the transatlantic community have seemed to be drifting further apart, which causes the development of alternative projects to maintain European security. This article aims to compare the current state of aff airs in the transatlantic and the European security systems, relying on the parameters, developed within the framework of the security communities theory, so as to access their feasibility and prospects. The author proceeds from the assumption that the relevant collective identity serves as a key factor for NATO’s and EU’s CFSP success and analyzes its ideational, institutional and practical components. New discourse is perceived as a starting point for transforming the identity of communities through formulating and justifying their main tasks. NATO is currently developing its new narrative while working on the alliance’s new strategic concept, with the EU elaborating on the idea of its “strategic autonomy”, creating a more vibrant and well-grounded story than NATO. However, to be translated into common practices the discourse should be rooted into a well-developed system of institutional communication channels, which is a distinctive feature of NATO, but not the EU. As a result, NATO’s experience in common practices, though not always successful and mutually complementing, creates an inertia within the community, providing for its stability and allowing for timely resolving inner confl icts. In this regard, the EU “strategic autonomy” is a matter of continuous systemic eff ort, rather than that of time.